2022
DOI: 10.3389/fpls.2022.819008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Development of Polymorphic Microsatellite Markers and Association Analysis of Major Agronomic Traits in Core Germplasm Resources of Tartary Buckwheat

Abstract: Tartary buckwheat (TB; Fagopyrum tataricum Gaertn.) is an important multigrain crop and medicinal plant, but functional genomics and molecular breeding research in this species have been lacking for quite some time. Here, genome-wide screening was performed to develop simple sequence repeat (SSR) markers associated with six major agronomic traits and the rutin contents of 97 core germplasm resources. A total of 40,901 SSR loci were identified; they were uniformly distributed throughout the TB genome, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(20 reference statements)
1
7
2
Order By: Relevance
“…Wood formation distinguishes woody from herbaceous plants, and represents a major metabolic sink for woody plants [ 17 ]. Several polymorphic SSR markers identified within genes associated with woody trait were helpful for marker-assisted breeding [ 17 , 20 , 21 ]. Lignin is the main component of secondary cell walls, and is essential for wood formation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wood formation distinguishes woody from herbaceous plants, and represents a major metabolic sink for woody plants [ 17 ]. Several polymorphic SSR markers identified within genes associated with woody trait were helpful for marker-assisted breeding [ 17 , 20 , 21 ]. Lignin is the main component of secondary cell walls, and is essential for wood formation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be inferred that SSRs we abundant in the whole genome of S. aralocaspica. Dinucleotide and trinucleotide repe were the most common SSRs in the genome of S. aralocaspica, similar to Tartary buckwh [30]. However, there is a difference in abundance between the two, as dinucleotide repe were the most common in Tartary buckwheat (63.95%), whereas trinucleotide repe were more common in S. aralocaspica (75.74%).…”
Section: Discussionmentioning
confidence: 92%
“…Several SSR markers have been developed and used to characterise the genetic diversity of common [ 60 , 61 , 62 , 63 ] and Tartary buckwheat [ 38 , 64 , 65 ]. Importantly, Hou et al [ 27 ] developed a large set of SSR markers through genome-wide screening and used them for genetic diversity analysis and marker-trait association to identify genomic regions associated with important agronomic traits in Tartary buckwheat. In our study, 25 SSR markers selected from the above studies were used to investigate the genetic diversity and structure of a large global collection of common and Tartary buckwheat.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other DNA-based markers, SSRs are best suited for characterising genetic diversity due to their high reproducibility, abundance, codominance, and multi-allelic inheritance [ 26 ]. In addition, Hou et al [ 27 ] have demonstrated the great utility of combining SSRs and agro-morphological markers in identifying genomic regions controlling important agronomic traits in Tartary buckwheat.…”
Section: Introductionmentioning
confidence: 99%